Analisis Volume Kendaraan Jl. Moch.Sruji – Jl.PB Sudirman. Pagi dan Sore Berdasarkan Data Lalu Lintas - Reynanta Raditya Gumilang; M. Rifki Alfaries; Amri Gunasti (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This study was conducted with the aim of analyzing the difference invehicle traffic volume in the morning and afternoon on the Moch.Sruji-Jalan PB.Sudirman road section in Jember Regency. The survey was conducted through field observationby directly recording vehicle volume at 15-minute intervalsminutes, covering four categories of vehicles: heavy vehicles, light vehicles, motorcycles, and non-motorized vehicles. The data obtained was analyzedusing a quantitative approach assisted by the SPSS application, including a normality testand a mean difference test to determine the significance of the difference invehicle volume between the two observation times. Descriptively, traffic flowin the morning had a higher volume, especially during peak hoursaround 06.00-08.00 with a total of 450-500 vehicles, whilein the afternoon it was in the range of 250-350 vehicles. In addition, motorcycleswere the most dominant type of vehicle in traffic flow compared toother vehicle categories. The conclusion of this study is that the pattern ofcommunity activity, which is more intense in the morning, makes this perioda peak hour with the potential to cause congestion. The results of this studyare expected to be taken into consideration in the formulation of targeted traffic engineering policiesin the study area.